Pendampingan Penyusunan RKPDes Tahun Anggaran 2023 di Desa Popisi, Kecamatan Banggai Utara Kabupaten Banggai Laut - Ade Putra Ode Amane; Salman Alfarizi Boliti; Haminun Dg Matorang; Laode Sabirila Jayalangi; Gisela Luigi Septiana (Yayasan Literasi Sains Indonesia, 2022)
The initial stages of village financial management are the planning, budgeting, administration, reporting, and accountability stages. Development planning for the next one year is compiled in the Village Development Work Plan (RKPDesa) document. Each village is required to prepare the RKPDesa as a form of development planning to be carried out and as the basis for the preparation of the Village Revenue and Expenditure Budget (APBDesa). Once the RKPDesa document is important and the activity is carried out every year, it is necessary to understand and know the stages of preparing the RKPDesa according to government regulations for the parties involved. Village development planning is contained in the Village Medium-Term Development Plan (RPJM-Desa) which is prepared every six years. RKP Desa is an elaboration of the RPJMDes with a period of 1 year which has been determined by village regulations. Of course, the synergy between the BPD as an element of the Implementation of Village Government and the Village Government cannot be separated. This article describes community service activities carried out by providing assistance in the preparation of the RKPDesa to village officials, the Village Representative Body (BPD), community leaders in Popisi Village, North Banggai District, Banggai Laut Regency.